2017
DOI: 10.1001/jamaophthalmol.2017.0561
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Manifestations of Congenital Zika Syndrome in Colombia and Venezuela

Abstract: The ocular manifestations and sequelae of Zika virus infection are not well known. Recently, the World Health Organization changed the declaration of Zika as a public health emergency and designated the viral outbreak and related microcephaly clusters as a long-term program of work. This change indicates the urgent need to evaluate and document ophthalmic manifestations in patients for timely management of this disease. In addition, confirmation whether the public health problem in Brazil extends to other regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 22 publications
1
71
0
2
Order By: Relevance
“…10,11,14,15 These ocular findings were first described after being identified in infants from the state of Pernambuco, which is located in northeastern Brazil, and were later supported by other publications from other states in Brazil, including Bahia, Ceará, and Rio de Janeiro. 10 -14 More recently, Yepez et al 20 reported similar ocular manifestations in affected infants from Colombia and Venezuela, which reinforces the consistency of these findings and the importance of ocular screening in newborns with a high suspicion for CZS.…”
Section: Ocular Findings In Czsmentioning
confidence: 70%
“…10,11,14,15 These ocular findings were first described after being identified in infants from the state of Pernambuco, which is located in northeastern Brazil, and were later supported by other publications from other states in Brazil, including Bahia, Ceará, and Rio de Janeiro. 10 -14 More recently, Yepez et al 20 reported similar ocular manifestations in affected infants from Colombia and Venezuela, which reinforces the consistency of these findings and the importance of ocular screening in newborns with a high suspicion for CZS.…”
Section: Ocular Findings In Czsmentioning
confidence: 70%
“…Significant outbreaks of ZIKV, a re-emerging mosquito-borne flavivirus, have occurred worldwide since 2013 [1,2]. Importantly, ZIKV infection has led to a global crisis due to its unexpected links to testis damage [3,4], ocular damage [5,6], Guillain-Barre syndrome, fetal microcephaly [1,[7][8][9], and potentially to other neural complications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently reported were macular atrophy, pigment mottling (63%), optic nerve anomalies (such as hypoplasia with double ring sign) (11%), lacunar maculopathy (6.9%), foveal reflex loss, and increased cupdisk ratio [31,43,54,55]. Additionally, Yepez et al [54] recently reported congenital glaucoma, corneal clouding, buphthalmos, increased intraocular pressure, and the clinical triad of epiphora, blepharospasm, and photophobia in infants with microcephaly.…”
Section: Congenital and Intrauterine Zika Virus Infectionmentioning
confidence: 99%